Bactris gasipaes fruits consumption by Caracara plancus in the Municipality of Brasiléia, southwestern Amazon, Brazil - Guilherme, Edson (2019)
The Southern Caracara (Caracara plancus) is a South American falconid that over the years has been colonizing open areas of the Southwestern Amazon. Regarding food habits, it is considered an opportunistic/generalist species. Caracara plancus has a varied diet, composed of animal protein, including carcasses. It also consumes plants, although this behavior appears less frequently in the scientific literature. Here we present a report of a Southern Caracara feeding on peach-palm fruits (Bactris gasipaes) in the rural area of Brasiléia, state of Acre, Brazil. The peach-palm tree is a common species, cultivated for obtaining heart of palm (“palmitos”) and fruits for consumption and regional marketing. Besides being a new food item in the Southern Caracara diet, the observed behavior indicates that C. plancus can potentially become a plague to the regional culture of peach-palm.